Allogenic endothelial progenitor cell transplantation increases flap survival through an upregulation of eNOs and VEGF on venous flap survival in rabbits. Issue 4 (April 2019) - Jin, Zeyuan; Yao, Chenglun; Poonit, Keshav; Han, Tao; Li, Sunlong; Huang, Zihuai; Yan, Hede
Summary: Background: Endothelial progenitor cells (EPCs) are one type of bone marrow hematopoietic stromal cells which play a vital role in neovascularization and tissue repair. In this study, we investigated whether EPCs promote flap survival in a rabbit venous model. Materials and methods: EPCs were customized from CHI Scientific, Inc, China. Thirty-six rabbits were randomly assigned to either the sham group ( n  = 12), the control group ( n  = 12) or the EPC transplantation group ( n  = 12). A 10 × 6 cm venous flap was created on the rabbit abdomen. Both the EPC transplantation and control groups had the same volume of EPCs–PBS (phosphate buffered saline) and PBS on postoperative day 1. Flap survival, blood flow, histopathology, expression of endothelial nitric oxide synthase (eNOs) and Vascular Endothelial Growth Factor (VEGF) were detected on postoperative day 10. Results: Cellular immunofluorescence assay positively confirmed that the EPCs were undergoing differentiation. The survival rate of the flap in the EPC transplantation group was 58.4 ± 7.1%, which was significantly higher than that of the control group (4.8 ± 3.4%) ( p <0.01). Histological examination revealed that the EPC transplantation group had higher microvessel density, fewer inflammatory cells, and a higher expression of eNOs and VEGF. Significantly increased blood flow perfusion was seen in the EPC transplantation group using laser Doppler imaging. The Western Blot technique revealed that the expression of eNOs and VEGF in the EPC transplantation group were both significantly higher than those in the control group. Conclusion: This study demonstrated that EPC transplantation improved venous flap survival in rabbits. The present findings may provide insight into the promotion of venous flap survival in clinical practice in the future.